Complications After Vaginal Vault Suspension Versus Minimally Invasive Sacrocolpopexy in Women With Elevated Body Mass Index: A Retrospective Cohort Study Using Data From the National Surgical Quality Improvement Program Database. Issue 6 (17th June 2022) - Stairs, Jocelyn; Minassian, Vatche; Clancy, Aisling
Abstract : Supplemental digital content is available in the text. Abstract : Importance: Overweight and obese women represent a growing share of pelvic floor reconstruction surgeons' practices. Determining perioperative risk specific to this population is essential to inform decision making regarding operative approach in this population. Objective: The aim of the study was to compare surgical complications among overweight and obese women undergoing apical compartment prolapse surgery by either minimally invasive abdominal or vaginal approach. Study Design: The American College of Surgeons National Surgical Quality Improvement Database was used to identify overweight and obese patients (body mass index ≥ 25) undergoing either minimally invasive sacrocolpopexy (MISC) or vaginal vault suspension (VVS) in the form of a sacrospinous vault fixation or uterosacral ligament fixation for pelvic organ prolapse from 2012 to 2019. Odds ratios for surgical complications, readmission, and reoperation were estimated using multivariable logistic regression. Results: Of 8, 990 eligible patients, 5, 851 underwent a VVS and 3, 139 patients underwent MISC. There was a greater odds of any complication in the first 30 days following VVS (n = 608 [10.4%]) compared with MISC (n = 247 [7.9%]; odds ratio, 1.27; 95% confidence interval, 1.08–1.48) on multivariable analysis. Urinary tract infections (UTIs) were the most common complication and were more likely following VVS (112 (3.6%) versus 350 (6.0%), P < 0.001). When UTIs were excluded, there was no difference in complications between approaches (1.00; 95% CI, 0.82–1.22). There were no statistically significant odds of readmission, reoperation, or serious complications between approaches. Conclusions: Vaginal vault suspension may be associated with a higher odds of any complication compared with MISC in overweight and obese women, but the rate of serious complications, readmission, and reoperation are low, and approaches were comparable when considering complications other than UTI.